2002
DOI: 10.1034/j.1600-0412.2002.810111.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐step test: the combined use of fetal fibronectin and sonographic examination of the uterine cervix for prediction of preterm delivery in symptomatic patients

Abstract: The proposed combined use of the cervical sonography and fetal fibronectin testing is a practical diagnostic tool for predicting preterm delivery with higher sensitivity and negative predictive value than any of these methods alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…In contrast, Crane and associates 25 and Hincz and associates 23 reported that funneling was not an independent predictor of preterm delivery in symptomatic women. Hincz and colleagues 23 also observed that there was a higher incidence of funneling with the advance of gestational age, a finding that was first seen by Iams 30 , who reported that funneling is probably normal after 32 weeks of gestation.…”
Section: Transvaginal Sonography In Women With Symptoms Of Preterm Labormentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, Crane and associates 25 and Hincz and associates 23 reported that funneling was not an independent predictor of preterm delivery in symptomatic women. Hincz and colleagues 23 also observed that there was a higher incidence of funneling with the advance of gestational age, a finding that was first seen by Iams 30 , who reported that funneling is probably normal after 32 weeks of gestation.…”
Section: Transvaginal Sonography In Women With Symptoms Of Preterm Labormentioning
confidence: 90%
“…Two other studies compared the diagnostic performance of cervicovaginal fetal fibronectin (fFN) and transvaginal sonographic evaluation of the uterine cervix in symptomatic patients. They reported that the combined use of cervical ultrasonography and fFN testing improved the diagnostic efficiency of any of these methods alone 22,23 . Rozenberg and co-workers 24 , in a similar study of 76 symptomatic patients, failed to show any significant additional benefit from the performance of fFN testing over the single transvaginal ultrasonographic measurement of cervical length.…”
Section: Transvaginal Sonography In Women With Symptoms Of Preterm Labormentioning
confidence: 99%
“…With this sequential combined approach, the sensitivity and NPV to predict delivery within 28 days increased to 86% and 97%, respectively. 19 Gomez et al 20 also suggested adding the FFN test to improve the prediction of preterm delivery when the TVCL is <30 mm. The FFN test is currently underutilised in public and private hospitals in Hong Kong.…”
Section: -17mentioning
confidence: 99%
“…Thus, the FFN test could be helpful in women with undetermined TVCLs. Hincz et al 19 suggested using the test in women with TVCLs of 21 to 31 mm. With this sequential combined approach, the sensitivity and NPV to predict delivery within 28 days increased to 86% and 97%, respectively.…”
Section: -17mentioning
confidence: 99%
“…Rizzo et al (1996) found that in the patients with cervical secretion fibronectin levels 60 ng/ml, survival analysis showed a shorter admission-to-delivery interval in the presence of an abnormal cervical index ( p 0.001). Hincz et al (2002) prospectively evaluated 82 patients with pre-term labour. In each case, fibronectin testing and sonographic examination of the cervix were performed.…”
Section: Economic Evaluationmentioning
confidence: 99%